Unveiling of the statue of Norman Washington Manley (Kingston : Jamaica Information Service (JIS), 1971)
Unveiling of the statue of national hero Norman Washington Manley at Victoria Park (now known as St. William Grant Park) which took place on his birthday July 4 in1971. Features a speech by then Governor-General Sir Florizel Glasspole.
Six (6) minutes and twenty-seven (27) seconds.
Also available as electronic reproduction.
Keywords: Manley, Norman Washington, -- 1893-1969.; Manley, Norman Washington, -- 1893-1969.